Experimental and numerical investigation of a counter-flow hollow fiber membrane-based evaporative cooler. Issue 1 (1st August 2022) - Yan, W C; Thiam, H S; Meng, X Z; Liu, Y L; Cui, X
Abstract: A counter-flow hollow fiber membrane-based evaporative cooler (HFMEC) was proposed. An experimental setup was developed to investigate the air handling performance of the HFMEC under various operating conditions. A numerical model was established and validated. The outlet air temperature predicted by the numerical model using free surface model showed a maximum deviation of 5% comparing with the experimental data. The model was further used to conduct a parametric analysis of the HFMEC. Six key parameters, including geometric specifications and operating conditions, were selected as factors for the sensitivity analysis. The cooling capacity and coefficient of performance (COP) were chosen as performance evaluation indicators. The simulation was performed with 27 cases for the orthogonal test. The range analysis revealed that the inlet air relative humidity and velocity, as well as packing fraction had significant impact on its cooling capacity and COP. Ranking the influence degree of key design parameters on performance evaluation indicators, this paper provides a convenient method to design and optimize the counter-flow HFMEC.